Dicamba Spray Drift as Influenced by Wind Speed and Nozzle Type - Alves, Guilherme Sousa; Kruger, Greg R.; Cunha, Joao Paulo A. R. da; Santana, Denise G. de; Pinto, Luis Andre T. [UNESP]; Guimaraes, Frederico; Zaric, Milos (Cambridge Univ Press, 2017)
With the release of dicamba-resistant crops, it is necessary to understand how technical and environmental conditions affect the application of dicamba. This study sought to evaluate drift from dicamba applications through flat-fan nozzles, under several wind speeds in a wind tunnel. Dicamba applications were performed through two standard (XR and TT) and two air induction (AIXR and TTI) 110015 nozzles at 0.9, 2.2, 3.6 and 4.9 Ms-1 wind speeds. The applications were made at 276 kPa pressure and the dicamba rate was 561 g ae ha(-1). The droplet spectrum was measured using a laser diffraction system. Artificial targets were used as drift collectors, positioned in a wind tunnel from 2 to 12m downwind from the nozzles. Drift potential was determined using a fluorescent tracer added to solutions, quantified by fluorimetry. The air induction TTI nozzle produced the lowest percentage of dicamba drift at 2.2, 3.6 and 4.9ms(-1) wind speeds at all distances. Dicamba spray drift from XR, TT and AIXR nozzles increased exponentially as wind speed increased, whereas from TTI nozzle drift increased linearly as wind speed increased. Drift did not increase linearly as the volume percentage of droplets smaller than 100 mu m and wind speed increased.
Keywords: Air induction nozzles; herbicide application technology; percent fines